THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND DIGITAL WORK COMPETENCE ON EMPLOYEE AGILITY: THE MEDIATING ROLE OF INNOVATIVE WORK BEHAVIOR - Pradhana, Fernanda Agung; Sudjadi, Achmad (Universitas Multimedia Nusantara, 2025)
Abstract- This study examines the influence of transformational leadership and digital work competence on employee agility through the mediating role of innovative work behavior among correctional institution employees in Central Java. In rapidly changing work environments, agility has become essential, particularly in public sector institutions characterized by rigid procedures and limited autonomy. Grounded in Work Adjustment Theory (P–E Fit), this study argues that leadership and digital competence may not directly enhance agility without the presence of innovative behavioral mechanisms. Using a quantitative approach and SEM–PLS with SmartPLS 4.0, data were collected from 50 correctional officers. The results reveal that digital work competence and transformational leadership do not have a direct significant effect on employee agility. Instead, both variables significantly influence innovative work behavior, which strongly predicts employee agility. Mediation analysis further shows that innovative work behavior provides full mediation in the relationships between transformational leadership and employee agility, as well as between digital work competence and employee agility. These findings underscore that innovation at the individual level is a critical pathway for developing agile employees in bureaucratic environments. The study contributes by highlighting innovation as a behavioral mechanism linking leadership and competence to agility and offers practical insights for fostering adaptive public-sector workforces. Keywords: Digital Work Competence; Employee Agility; Innovative Work Behavior; Transformational Leadership